Impact of dialysis in patients undergoing bioprosthetic aortic valve replacement. (7th May 2021) - Kuroda, Yuki; Marui, Akira; Arai, Yoshio; Nagasawa, Atsushi; Tsumaru, Shinichi; Arakaki, Ryoko; Iida, Jun; Wada, Yuki; Tamai, Yumeka; Fukushima, Takashi; Soga, Yoshiharu
Abstract:  : OBJECTIVES: To determine the incidence of bioprosthetic structural valve deterioration in dialysis patients undergoing aortic valve replacement compared to that in patients without dialysis. METHODS: This single-centre retrospective observational study included 1159 patients who underwent aortic valve replacement using bioprosthetic valves for aortic stenosis and/or regurgitation at our institution between 2007 and 2017 [patients with dialysis (group D, n  = 134, 12%) or without dialysis (group N, n  = 1025, 88%)]. To adjust for potential differences between groups in terms of initial preoperative characteristics or selection bias, a propensity score analysis was conducted. The final sample that was used in the comparison included 258 patients, as follows: 129 patients with dialysis (group D) and 129 patients without dialysis (group N). The cumulative incidences of all-cause death, cardiac death and moderate or severe structural valve deterioration were estimated using the Kaplan–Meier method. RESULTS: Operative mortality was significantly higher in group D than group N (9% vs 0%, P  =   0.001). Kaplan–Meier analysis revealed that in group D, the incidence was significantly higher for all-cause death ( P  <   0.001, 50% vs 18% at 5 years), cardiac death ( P  =   0.001, 18% vs 5% at 5 years) and moderate or severe structural valve deterioration ( P  <   0.001, 29% vs 5% at 5 years) compared with group N. CONCLUSIONS: The incidence of structural valve deterioration in dialysis patients undergoing aortic valve replacement was higher than that in patients without dialysis. Bioprosthetic valves should be carefully selected in dialysis patients undergoing aortic valve replacement.